2005
DOI: 10.1891/vivi.2005.20.5.529
|View full text |Cite
|
Sign up to set email alerts
|

The Composite Abuse Scale: Further Development and Assessment of Reliability and Validity of a Multidimensional Partner Abuse Measure in Clinical Settings

Abstract: Absence of a well-validated comprehensive partner abuse questionnaire has been a major methodological issue in domestic violence research. A new multidimensional measure of partner abuse, the Composite Abuse Scale (CAS), has four dimensions: Severe Combined Abuse, Emotional Abuse, Physical Abuse, and Harassment. A general practice patient sample (N = 1,836) has been used in the development and testing of CAS. Factor analyses in this current study confirmed the four dimensions from a preliminary nurses sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
229
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(231 citation statements)
references
References 23 publications
1
229
0
1
Order By: Relevance
“…A total summative score can be derived, with higher scores indicative of greater severity of abuse [57]. The CAS has demonstrated good internal consistency [58] and evidence of content, construct, criterion, and factorial validity [59]. In this study, the 3 sexual abuse items were modified to make them more consistent with current theory and measurement approaches in the field [60].…”
Section: Methodsmentioning
confidence: 99%
“…A total summative score can be derived, with higher scores indicative of greater severity of abuse [57]. The CAS has demonstrated good internal consistency [58] and evidence of content, construct, criterion, and factorial validity [59]. In this study, the 3 sexual abuse items were modified to make them more consistent with current theory and measurement approaches in the field [60].…”
Section: Methodsmentioning
confidence: 99%
“…Evaluations of screening tools in primary and secondary health care settings have shown that several scales provide reasonable accuracy in detecting abuse (Wathen & MacMillan, 2003), though there has been less evaluation of these tools in patients with severe mental illness. Some 'gold standard' scales exist including the Composite Abuse Scale, a validated 30-item scale measuring four dimensions of abuse inflicted on a woman by her partner: physical abuse, emotional abuse, severe combined abuse and harassment (Hegarty, Sheehan, & Schonfeld, 1999, Hegarty, Fracgp, Bush, & Sheehan, 2005. We have used this scale in our recent research and found it to be acceptable to patients with severe mental illness, with good rates of completion .…”
Section: What Are the Impacts On Physical And Mental Health?mentioning
confidence: 99%
“…(APQ) [107]MParentingAdult Rejection Sensitivity Q. (ARSQ) [108]MSymptoms/BehaviourAlcohol, Smoking and Substance Involvement Screening Test (ASSIST) [109]MSubstance UseBeck Anxiety Inventory (BAI) [110]MSymptomsComposite Abuse Scale (CAS) [111]MAbuse – Family Environ.Child Behaviour Checklist (CBCL) [112]CSymptomsConflict Behaviour Q. (CBQ) [113]M/CFamily EnvironmentCoping with Children’s Negative Emotions Scale (CCNES) [114]MParentingChildren’s Depression Inventory – Parent (CDI-2-P) [115]CSymptomsCentre for Epidemiologic Studies Depression Scale (CESD) [116]MSymptomsChild Health Q.…”
Section: Methodsmentioning
confidence: 99%